2021
DOI: 10.1017/ssh.2021.16
|View full text |Cite
|
Sign up to set email alerts
|

Varieties of Social Democracy and Cooperativism: Explaining the Historical Divergence between Housing Regimes in Nordic and German-Speaking Countries

Abstract: The historical-comparative study of social democracy and cooperative organization are the foster children of historical sociology. This article offers a first account of systematic ideological differences in social-democratic ideology regarding private ownership and different cooperative traditions in the housing sphere of Northern European and continental German-speaking countries. The long-run trajectory of housing welfare regimes in these two country groups has been one of divergence: Nordic countries have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…1 If the type of national housing system matters for the development trajectory of social housing, as some authors have suggested (see e.g. Kohl & Sørvoll, 2021), we would expect diverging developments in the two cities. Second, we analyze our cases through a multi-dimensional framework of social housing decline/stability that we present below.…”
Section: Introductionmentioning
confidence: 99%
“…1 If the type of national housing system matters for the development trajectory of social housing, as some authors have suggested (see e.g. Kohl & Sørvoll, 2021), we would expect diverging developments in the two cities. Second, we analyze our cases through a multi-dimensional framework of social housing decline/stability that we present below.…”
Section: Introductionmentioning
confidence: 99%